Analysis of Consumer Price Index Changes at Mataram City in 2023-2024 - Maulani, Septia Hasna; Robbaniyyah, Nuzla Af'idatur (JSN : Jurnal Sains Natural, 2025)
This research aims to analyze the development of the Consumer Price Index (CPI) in Mataram City from January to September in 2023 and 2024. In addition, this study also aims to identify and analyze certain patterns or trends in the CPI comparison between the two years. This research also evaluates and explains the implications of CPI differences for the local economy. These include the impact on people's purchasing power, consumption patterns, and the affected economic sectors. The analytical methods used include descriptive and quantitative analysis by utilizing secondary data. The results show that there is a significant difference in the CPI between 2023 and 2024. The average CPI in January to September 2023 is 113.69, which is higher than the same period in 2024 which has an average of 106.03. This difference indicates that the cost of living in 2023 is higher, while the decrease in CPI in 2024 has the potential to increase people's purchasing power. These findings have important implications for the local economy in Mataram City, including changes in consumption patterns and impacts on various economic sectors.